2006
DOI: 10.1161/01.atv.0000202028.62414.3c
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis in Mice Is Not Affected by a Reduction in Tissue Factor Expression

Abstract: Objective-To determine whether tissue factor (TF) contributes to the progression of atherosclerotic lesions in mice. Methods and Results-We determined the effect of a 50% reduction of TF levels in all cells on atherosclerosis in apolipoprotein E-deficient (apoE Ϫ/Ϫ ) mice. No differences were observed in the extent of atherosclerosis in apoE Ϫ/Ϫ /TF ϩ/ϩ and apoE Ϫ/Ϫ /TF ϩ/Ϫ mice fed regular chow for 34 weeks. Atherosclerosis could not be analyzed in apoEmice expressing low levels of TF because of premature dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 51 publications
2
28
1
Order By: Relevance
“…In previous studies it was determined that a 50% reduction of TF, in all cells or in hematopoietic cells only in ApoE−/− and LDLR−/− mice, respectively, does not affect atherosclerosis development 50 . In our study we found that asTF overexpression increase neointima formation and lesion’s neovascularization following arterial injury in ApoE−/− mice fed a Western-type diet.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies it was determined that a 50% reduction of TF, in all cells or in hematopoietic cells only in ApoE−/− and LDLR−/− mice, respectively, does not affect atherosclerosis development 50 . In our study we found that asTF overexpression increase neointima formation and lesion’s neovascularization following arterial injury in ApoE−/− mice fed a Western-type diet.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, newly formed microvessels within atherosclerotic plaques can lead to plaque growth and destabilization by promoting inflammation and haemorrhage, and TF, which is importantly involved in angiogenesis [95], may play a role in plaque neovascularization. Nevertheless, the development of atherosclerosis in heterozygous TF-knockout mice, which have a 50 % reduction in vascular TF activity, does not differ from that in control animals; moreover, a 90 % reduction in haematopoietic-cell-derived TF does not alter the development of atherosclerotic lesions either [145]. Thus TF does not appear to influence atherogenesis in mice under these conditions.…”
Section: Tf and Atherosclerosismentioning
confidence: 88%
“…Tilley et al used heterozygous TF knockout mice, which exhibit either 50% reduction in vascular TF activity or a 90% reduction in hematopoietic cell-derived TF, and investigated the development of atherosclerotic lesions. Interestingly, equal amount of atherosclerotic lesions were observed in these mice, 110 raising the question whether TF, at least in rodents, plays a role in atherogenesis, or not. This question still needs to be further investigated.…”
Section: Tf and Atherosclerosismentioning
confidence: 96%